Effectiveness of Treating Foot-And-Mouth Disease Syndrome in Cattle Using Extracts of Binahong Leaves, Cassava Arabica, and Turmeric - Euis Nia Setiawati; Ibnu Mahmudin; Vony Armelia (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2025)
Foot-and-Mouth Disease (FMD) in livestock is an infectious disease caused by a virus from the Aphtovirus genus. It affects ruminant animals (such as cattle, buffalo, goats, sheep, deer), pigs, camels, and several species of wild animals. This disease often worsens when secondary bacterial infections occur. Theoretically, FMD cannot be cured because it is caused by a virus. This study aims to evaluate the management of FMD cases through symptomatic, supportive, antibiotic treatments, and the use of herbal medicines to prevent secondary infections. Three treatment groups were established: Group 1 received pharmaceutical treatment (injection of vitamins and antibiotics, and spraying of wounds with physiological NaCl solution); Group 2 received treatment with extracts of binahong leaves, cassava arabica leaves, and turmeric; and Group 3 received a combination of pharmaceutical treatment (injection of vitamins and antibiotics, and wound spraying with NaCl solution) along with herbal treatment. For the combination group, wounds on the feet and mouth were sprayed three times daily with a clean condition maintained, using a mixture of binahong, cassava arabica, and turmeric extract (BSK extract). Additionally, 1000 ml of BSK decoction was administered orally at each treatment session, concurrent with wound care, for five consecutive days. Statistical analysis of the results showed that treatment in Group 3 (pharmaceutical combined with BSK extract) resulted in a significantly better healing rate (p < 0.05) for lesions on the mouth, gums, and feet compared to the control group (pharmaceutical treatment alone) and Group 2 (BSK extract treatment alone). However, further research with a larger number of cattle is necessary to obtain more comprehensive and optimal results.